From the Common Security and Defence Policy to the Common Army - Vojtech Jurčák; Radoslav Ivančík (Vojenské rozhledy, 2023)
Voices about the need to build a joint European Union army have been appearing on the European scene for several years, but recently these voices have become stronger, especially after the Russian invasion of Ukraine. Therefore, in the article, the authors deal with the issue of the possibility of creating a common European army. They draw on from socio-scientific political science approaches to current security frameworks, examine the current state, and at the same time point out that, despite the threats Europe is facing, there is still no clear plan for how such an army should be created. Considering the facts mentioned in the article, the authors state that the creation of a common European army, at least for now, seems unlikely, as a supranational model of the European army would require the transfer of sensitive national competences from the member states to the EU level.